Effect of Prenatal Polycyclic Aromatic Hydrocarbons Exposure on Birth Outcomes: The Polish Mother and Child Cohort Study. (22nd July 2014) - Polanska, Kinga; Dettbarn, Gerhard; Jurewicz, Joanna; Sobala, Wojciech; Magnus, Per; Seidel, Albrecht; Hanke, Wojciech
Abstract : The aim of this study was to assess the impact of PAH exposure on various anthropometric measures of birth outcomes. The study population consisted of 210 nonsmoking pregnant women. Urine samples collected between 20th and 24th week of pregnancy were used for analysis of the following PAH metabolites: 1-, 2-, 3-, 4-, and 9-hydroxyphenanthrene (1-, 2-, 3-, 4-, and 9-OH-PHE), 1-hydroxypyrene (1-OH-PYR), 1, 6 + 1, 8-dihydroxypyrene (DI-OH-PYR), phenanthrene trans -1, 2-dihydrodiol (PHE-1, 2-diol), and phenanthrene trans -9, 10-dihydrodiol (PHE-9, 10-diol) by gas chromatography-mass spectrometry. Environmental tobacco smoke exposure (ETS) was assessed by cotinine level in saliva using a stable isotope dilution LC-ESI-MS/MS method. The mean PAH metabolite concentrations were in the range of 0.15 µ g/g creatinine for 9-OH-PHE to 5.9 µ g/g creatinine for PHE-9, 10-diol. It was shown that none of the individual PAH exposure markers demonstrate a statistically significant influence on birth outcomes. Interestingly a statistically significant association was found between the sum of OH-PHE along with cotinine level and the cephalization index after adjusting for potential confounders (P = 0.04 ). This study provides evidence that combined exposure of pregnant women to common environmental pollutants such as PAH and ETS might adversely affect fetal development. Thus, reduction of human exposure to these mixtures of hazardous compounds would in particular result in substantial health benefits for newborns.